2015
DOI: 10.2319/042415-279.1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer accuracy of vinyl polysiloxane trays for indirect bonding

Abstract: Objective: To elicit the magnitude, directional bias, and frequency of bracket positioning errors caused by the transfer of brackets from a dental cast to the patient's dentition in a clinical setting. Materials and Methods: A total of 136 brackets were evaluated. The brackets were placed on dental casts and scanned using cone beam computed tomography (CBCT) to capture 3-D positioning data. The brackets were then transferred to the patient's dentition with an indirect bonding method using vinyl polysiloxane (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 15 publications
11
92
1
6
Order By: Relevance
“…In recent years, a variety of devices or transfer trays have been developed to accurately transfer the ideal bracket placement to patients' dentitions. 2,4,[6][7][8][9]12,13,[15][16][17] However, the effectiveness of such devices might be questioned without proper procedures for precise control and prediction of possible complications. Based on the 3D assessment, we found that the protocol in this study allowed accurate transfer of bracket placement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, a variety of devices or transfer trays have been developed to accurately transfer the ideal bracket placement to patients' dentitions. 2,4,[6][7][8][9]12,13,[15][16][17] However, the effectiveness of such devices might be questioned without proper procedures for precise control and prediction of possible complications. Based on the 3D assessment, we found that the protocol in this study allowed accurate transfer of bracket placement.…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of digital technology, 3D assessment using the scanned model has been proposed to be more accurate than 2D assessment using digital photography. 5,[13][14][15]18 In this study, a semiautomated 3D measurement in Geomagic Studio 2013 was used to measure the position and orientation deviations for 205 brackets. Because the local coordinate system had been prelocated on the bracket, there was no need to identify the corresponding reference points on the teeth from different patients repeatedly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations